Chitosan-copper / zinc-based hybrid nanoflower material, preparation method and application
A low-cost self-assembly method synthesizes chitosan-copper/zinc-based hybrid nanoflowers, enhancing antibacterial properties and addressing Rhizoctonia solani infection, while serving as a nanofertilizer for improved crop growth.
Patent Information
- Application Number
- CN202411126368.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-17
AI Technical Summary
The synthesis of chitosan-metal hybrid nanoflowers through a simple and low-cost self-assembly method has not been developed, and the combination of two metal elements for nanoflower synthesis is insufficient, especially in the field of agricultural antibacterial applications, particularly for Rhizoctonia solani infection prevention and treatment.
A method involving dissolving chitosan in acetic acid, adding copper salt and phosphate to form chitosan-copper hybrid nanoflowers, followed by modification with zinc oxide nanoparticles, to create a chitosan-copper/zinc-based hybrid nanoflower material with enhanced antibacterial properties.
The material effectively prevents Rhizoctonia solani infection, acts as a nanofertilizer, and overcomes issues of easy inactivation and drug resistance, providing a sustainable solution for agricultural disease prevention with low-volume and high-efficiency.
Smart Images

Figure CN119138412A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano pesticides, and specifically relates to a chitosan-copper / zinc-based hybrid nanoflower material, a preparation method and an application thereof. Background Art
[0002] As a new type of pesticide, nanopesticide has an efficacy that is about 30% higher than that of traditional pesticides. Copper-based and zinc-based nanomaterials have great application potential in agriculture due to their excellent targeted delivery capabilities and antibacterial properties. In addition, these materials can also be used as nanofertilizers and nanoregulators to improve the stress resistance and yield of crops. However, the dosage control of copper-based and zinc-based nanomaterials is difficult, and they have potential environmental toxicity, which limits their large-scale application.
[0003] Chitosan and its derived nanomaterials have good prospects in agricultural antibacterial. Studies have shown that the inhibitory effects of chitosan / iron oxide composite nanomaterials and chitosan / titanium dioxide composite nanomaterials on Xanthomonas are better than those of single materials, which may be due to the synergistic effect between chitosan and metal materials that enhances the antibacterial effect. Organic-metal hybrid nanoflowers have attracted widespread attention in the fields of catalysis, drug carriers and electrode materials due to their high activity and large specific surface area, but they are still in the early stages in the field of antibacterial. The traditional organic components of organic-metal hybrid nanoflowers (such as DNA and protein) are easily inactivated and have high costs. Chitosan can be used as an organic component for the synthesis of organic-metal hybrid nanoflowers because it has hydroxyl, amide and amino groups necessary for interaction with metal ions. At present, some researchers have explored and studied related materials, as shown below: CN116511516B discloses a new type of copper-based nanomaterial and its application in anti-oxidation and antibacterial. For the first time, two copper-based nanomaterials CSIA-Cu@Pt and CSIA-Cu@Ag were synthesized by chemical reduction method using double-stranded nucleic acid products as templates. It was also found that CSIA-Cu@Pt has peroxidase-like activity, and the antibacterial mechanism is mainly due to the addition of nanomaterials causing oxidative stress inside bacteria, which in turn causes oxidative damage to DNA and causes bacterial rupture. CN114875674B discloses a method for preparing antibacterial wool fabric loaded with polyvinyl pyrrolidone / copper metal organic framework, and the antibacterial rate of the material against Staphylococcus aureus and Escherichia coli reaches 99.9%; CN113244393B discloses a method for preparing a titanium dioxide nanotube / molybdenum disulfide nanoflower complex.
[0004] Although the potential of chitosan as an organic ingredient has been widely recognized, the technology for synthesizing chitosan-metal hybrid nanoflowers through a simple and low-cost self-assembly method has not yet been developed. In addition, the research on the combination of two metal elements for nanoflower synthesis is still insufficient, especially in the field of prevention and treatment of agricultural Rhizoctonia solani infection. Therefore, it is urgent to develop a new preparation method of chitosan-copper / zinc-based hybrid nanoflower material and use it in the field of agricultural antibacterial. Summary of the invention
[0005] The purpose of the present invention is to solve the deficiencies in the prior art and provide a chitosan-copper / zinc-based hybrid nanoflower material, a preparation method and an application thereof.
[0006] The specific technical solutions adopted by the present invention are as follows:
[0007] In the first aspect, the present invention provides a method for preparing a chitosan-copper / zinc-based hybrid nanoflower material, the specific steps of which are as follows:
[0008] S1: dissolving chitosan in an acetic acid solution to obtain a chitosan solution; adding copper salt and phosphate solution to the chitosan solution, mixing them evenly to obtain a reaction system for self-assembly reaction, washing and drying the reaction product to obtain chitosan-copper-based hybrid nanoflowers;
[0009] S2: Disperse zinc oxide nanoparticles in an ethanol solution, add the chitosan-copper-based hybrid nanoflowers prepared in step S1, mix well and then shake to react, modify the chitosan-copper-based hybrid nanoflowers with zinc oxide nanoparticles, wash and dry the reaction product to obtain a chitosan-copper / zinc-based hybrid nanoflower material.
[0010] Preferably, the concentration of chitosan in step S1 is 1.25-5 mM.
[0011] Preferably, the concentration of copper ions in the reaction system in step S1 is 1-40 mM, and the concentration of phosphate is 0.05-0.1 mM.
[0012] Preferably, the copper salt in step S1 is copper sulfate or copper nitrate.
[0013] Preferably, the pH value of the self-assembly reaction in step S1 is controlled at 7 to 8, and the reaction time is 36 to 96 hours.
[0014] Preferably, the volume percentage concentration of the acetic acid solution in step S1 is 2%; the volume percentage concentration of the ethanol solution in step S2 is 20%.
[0015] Preferably, in step S2, the mass ratio of chitosan-copper-based hybrid nanoflowers to zinc oxide nanoparticles is (7-20):1.
[0016] Preferably, the shaking reaction in step S2 is carried out at 25±2° C. and 180 rpm for 8 to 12 hours.
[0017] In a second aspect, the present invention provides a chitosan-copper / zinc-based hybrid nanoflower material obtained by the preparation method described in the first aspect.
[0018] In the third aspect, the present invention provides an application of the chitosan-copper / zinc-based hybrid nanoflower material described in the second aspect in agricultural antibacterial treatment, characterized in that the chitosan-copper / zinc-based hybrid nanoflower material is sprayed onto crops infected with pathogenic bacteria, and the concentration of the chitosan-copper / zinc-based hybrid nanoflower material is 10 to 100 mg / L.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention uses chitosan as an organic component and combines it with copper phosphate through a self-assembly method to successfully synthesize chitosan-copper-based hybrid nanoflower materials with micro-nano flower-like structures. The preparation method is simple, low-cost, and effectively utilizes the natural biocompatibility and biodegradability of chitosan. Compared with the easily inactivated organic components (such as DNA, protein, etc.) commonly used in traditional organic-inorganic hybrid nanoflowers, the present invention has opened up a new direction for the synthesis of organic-inorganic hybrid nanoflowers.
[0021] (2) Based on chitosan-copper hybrid nanoflowers, the present invention further modifies zinc oxide nanoparticles to prepare chitosan-copper / zinc hybrid nanoflower materials. This innovative combination of bimetallic nanomaterials cleverly combines the antibacterial properties of copper and zinc, significantly improving the antibacterial properties of the material. Compared with traditional pesticides, this material overcomes the problems of easy inactivation and drug resistance, while solving the potential environmental toxicity of copper-based and zinc-based nanomaterials, showing the characteristics of low-volume and high-efficiency, and reducing environmental risks.
[0022] (3) The chitosan-copper / zinc-based hybrid nanoflower material prepared by the present invention can not only effectively prevent and control crop infection with Rhizoctonia solani, but also can be used as a nanofertilizer to promote crop growth, greatly improving the practicality of the material and providing an efficient and sustainable solution for agricultural disease prevention and control. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1The surface scanning electron micrographs of chitosan-copper hybrid nanoflowers prepared under different conditions in Example 1, wherein (a) to (d) are chitosan concentrations of 1.25, 2.5, 5 and 10 mM, respectively; (e) to (h) are copper sulfate concentrations of 1, 5, 20 and 40 mM, respectively; (i) to (l) are self-assembly reaction pH values of 6, 7, 8 and 9, respectively; and (m) to (p) are phosphate concentrations of 0, 0.05, 0.1 and 0.15 mM, respectively;
[0024] Figure 2 This is a scanning electron microscope image of the chitosan-copper-based hybrid nanoflower material prepared by first adding chitosan solution and then adding copper sulfate and phosphate in Example 1;
[0025] Figure 3 This is a scanning electron microscope image of the chitosan-copper / zinc-based hybrid nanoflower material prepared in Example 1 at a mass ratio of chitosan-copper-based hybrid nanoflower to zinc oxide nanoparticles of 9:1;
[0026] Figure 4 The X-ray diffraction diagram of the chitosan-copper / zinc-based hybrid nanoflower material prepared in Example 1 with a mass ratio of chitosan-copper-based hybrid nanoflower to zinc oxide nanoparticles of 9:1;
[0027] Figure 5 This is a diagram showing the effect of chitosan-copper / zinc-based hybrid nanoflower materials with different material ratios in Example 2 on inhibiting Rhizoctonia solani;
[0028] Figure 6 (a) The inhibitory effect of different concentrations of chitosan-copper / zinc-based hybrid nanoflower materials on Rhizoctonia solani in Example 2, and (b) the half-effective concentration curve of the material.
[0029] Figure 7 The effect of chitosan-copper / zinc-based hybrid nanoflowers on the mycelium morphology and reactive oxygen production of Rhizoctonia solani in Example 3, wherein (a) is a scanning electron micrograph of the mycelium of Rhizoctonia solani in the control group, (b) and (b-1) are reactive oxygen analyses of the mycelium of Rhizoctonia solani in the control group, (c) is a scanning electron micrograph of the mycelium of Rhizoctonia solani after treatment with chitosan-copper / zinc-based hybrid nanoflowers, and (d) and (d-1) are reactive oxygen analyses of the mycelium of Rhizoctonia solani after treatment with chitosan-copper / zinc-based hybrid nanoflowers. DETAILED DESCRIPTION
[0030] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0031] Example 1
[0032] This embodiment provides a method for preparing chitosan-copper / zinc-based hybrid nanoflower materials with different material ratios, as follows:
[0033] (1) Chitosan-copper hybrid nanoflowers were prepared, and their morphology and particle size were precisely controlled by adjusting the chitosan concentration (1.25, 2.5, 5, and 10 mM), copper sulfate concentration (1, 5, 20, and 40 mM), phosphate concentration (0, 0.05, 0.1, and 0.15 mM), pH value (6, 7, 8, and 9), and the order of reagent addition, as follows:
[0034] Chitosan of different masses was added to a 2% (v / v) acetic acid solution and stirred at 25±2°C for 24 hours until completely dissolved to obtain chitosan solutions of different concentrations. Copper sulfate and phosphate solutions of different concentrations were added in sequence, and the total volume was adjusted to 30 mL after adjusting the pH value. The mixture was vortexed for 1 minute to ensure sufficient mixing, and then reacted at 25±2°C for 72 hours for self-assembly and co-precipitation. Finally, the reaction product was centrifuged at 4000r / min for 5 minutes, the precipitate was washed twice with ethanol and dH2O, and freeze-dried at -80°C for 24 hours to obtain chitosan-copper-based hybrid nanoflowers of different morphologies and particle sizes. The scanning electron microscope image is as follows Figure 1 shown.
[0035] Effect of chitosan concentration: Figure 1 As shown in (a) to (c), when the chitosan concentration increases from 1.25mM to 5mM, the size of the chitosan-copper hybrid nanoflowers decreases significantly. However, when the chitosan concentration continues to increase to 10mM, the material agglomerates significantly due to the aggregation effect between molecules, as shown in Figure 1 (d).
[0036] Effect of copper sulfate concentration: When the copper sulfate concentration was 5 mM, the nucleation rate of chitosan-copper-based hybrid nanoflowers was slow, resulting in larger and non-uniform sizes, e.g. Figure 1 (e). As the concentration of copper sulfate increases to 20 mM and 40 mM, the size of chitosan-copper-based hybrid nanoflowers decreases and becomes uniform, e.g. Figure 1 (f) and (g). However, when the copper sulfate concentration reached 60 mM, flocculent deposits formed on the surface of the material, such as Figure 1 (h).
[0037] Effect of pH value: When the pH value of the self-assembly reaction is in the range of 7 to 8, the structure of chitosan-copper-based hybrid nanoflowers is more compact and uniform, such as Figure 1 (i) to (k). When the pH value is further increased to 9, cracks appear on the surface of the nanoflowers, probably due to the repulsion of chitosan molecules caused by the high pH. Figure 1 (l).
[0038] Effect of phosphate concentration: As the phosphate concentration increases from 0 to 0.1 mM, the morphology of chitosan-copper hybrid nanoflowers gradually improves. Figure 1 (n)~(o). However, when the phosphate concentration is 0.2mM, the phosphate concentration may be too high, which may cause the precipitation or flocculation of the substances in the solution, and the material appears as a flocculent and unformed substance. Figure 1 (p).
[0039] Effect of the order of reagent addition: Figure 2 The scanning electron micrograph of chitosan-copper hybrid nanoflower material prepared by first adding chitosan solution and then adding copper sulfate and phosphate shows that this addition sequence helps to form a more ordered structure and obvious petal-like morphology. The particle size of chitosan-copper hybrid nanoflower is maintained between 4 and 6 μm. Figure 1 (l) is a scanning electron micrograph of chitosan-copper hybrid nanoflower material prepared by first adding copper sulfate and phosphate and then adding chitosan solution. The generated chitosan-copper hybrid nanoflower has poor morphology and a particle size range of 7-12 μm.
[0040] In summary, the optimal preparation conditions of chitosan-copper hybrid nanoflowers are: chitosan concentration 5mM, copper sulfate concentration 40mM, pH 7-8, phosphate concentration 0.1mM. In addition, adding chitosan first and then adding phosphate and copper sulfate is more conducive to the formation of flower-like morphology of chitosan-copper hybrid nanoflowers. Therefore, the above preparation conditions were used in the subsequent preparation.
[0041] (2) Take the chitosan-copper hybrid nanoflowers obtained under the optimal preparation conditions of step (1), and set the mass ratio of chitosan-copper hybrid nanoflowers to zinc oxide nanoparticles to 7:1, 8:1, 9:1, 10:1, 15:1, and 20:1, respectively. Disperse the zinc oxide nanoparticles in a 20% (v / v) ethanol solution and ultrasonicate for 10 min to ensure that the material is fully dispersed. According to the set mass ratio, add appropriate amounts of zinc oxide nanoparticles one by one and ultrasonicate again for 5 min, shake and react at 25°C for 8 h, and use zinc oxide nanoparticles to modify chitosan-copper hybrid nanoflowers. After washing and drying the reaction product, chitosan-copper / zinc-based hybrid nanoflower materials are obtained.
[0042] Figure 3 This is a scanning electron microscope image of the chitosan-copper / zinc-based hybrid nanoflower material prepared at a mass ratio of 9:1 between chitosan-copper-based hybrid nanoflowers and zinc oxide nanoparticles. Figure 4 is the X-ray diffraction pattern of the material.
[0043] according to Figure 3As shown, the prepared chitosan-copper / zinc-based hybrid nanoflower material has uniform size, smooth surface and regular morphology. Figure 4 This indicates that the material has a good crystal structure, and the characteristic diffraction peaks of zinc oxide nanoparticles can be observed, indicating that zinc oxide nanoparticles have been successfully loaded into the material. Scanning electron microscopy and X-ray diffraction characterization further confirmed the nanostructure and crystal properties of chitosan-copper / zinc-based hybrid nanoflower materials, providing structural support for their performance in antibacterial applications.
[0044] Example 2
[0045] This example uses the chitosan-copper / zinc-based hybrid nanoflower material prepared in Example 1 to measure the effect of inhibiting Rhizoctonia solani, as follows:
[0046] Different concentrations of chitosan-copper / zinc-based hybrid nanoflower materials were added to potato dextrose agar (PDA) solid culture medium, ranging from 5, 10, 25, 50 and 100 mg / L to evaluate their inhibitory effects on Rhizoctonia solani. A 4-day-old Rhizoctonia solani mycelial disk with a diameter of 7 mm was inoculated into the center of a PDA culture medium containing different concentrations of chitosan-copper / zinc-based hybrid nanoflower materials. These plates were cultured at 25±2°C for 6 days. dH2O was used as a control sample for this experiment. The antibacterial effect was evaluated by measuring the diameter of the mycelium. The mycelial diameter was determined using the cross method, and the inhibition rate was calculated. The formula is:
[0047]
[0048] Figure 5 The results show that the inhibition rate of chitosan-copper hybrid nanoflowers and zinc oxide nanoparticles is the best when the mass ratio of chitosan-copper hybrid nanoflowers to zinc oxide nanoparticles is 8:1 and 9:1. Considering the cost and preparation efficiency of the materials, the mass ratio of 9:1 is selected as the optimal ratio.
[0049] Figure 6(a) shows the inhibitory effect of chitosan-copper / zinc-based hybrid nanoflower materials of different concentrations (the mass ratio of chitosan-copper-based hybrid nanoflowers to zinc oxide nanoparticles is 9:1) on Rhizoctonia solani. When the concentration is 100 mg / L, the inhibition rate reaches 74.17%, which is significantly better than chitosan-copper-based hybrid nanoflowers and zinc oxide nanoparticles used alone. Through logistic curve analysis, the half effective concentration (EC50) of the material is 45.39 mg / L, as shown in Figure 2. Figure 6 (b).
[0050] Example 3
[0051] This example studies the effects of the chitosan-copper / zinc-based hybrid nanoflower material prepared in Example 1 on the morphology and physiological state of Rhizoctonia solani, as follows:
[0052] Mycelium treatment and morphological observation: A mycelium block of Rhizoctonia solani with a diameter of 7 mm was placed in a potato dextrose (PDB) medium and cultured on an oscillator at 25±2°C and 150rpm for 48h. Subsequently, the mycelium was obtained by centrifugation and rinsed three times with PBS buffer, and resuspended in a 0.1M PBS solution to obtain a mycelium suspension. Take an appropriate amount of mycelium suspension and prepare a PBS solution containing 45mg / L chitosan-copper / zinc-based hybrid nanoflower material, and culture it at 25±2°C and 150rpm for 9h. The control group was treated in the same way in PBS without chitosan-copper / zinc-based hybrid nanoflower material. After the culture, the mycelium was washed three times with PBS and fixed overnight with 2.5% glutaraldehyde at 4°C. Dehydrate with different concentrations of ethanol (30%, 50%, 70%, 80%, 90%, 100%) for 15 minutes each time; then dehydrate with 100% ethanol twice, 20 minutes each time; then dehydrate with 50% tert-butanol for 30 minutes; finally dehydrate with 100% tert-butanol overnight. Transfer the sample to fresh tert-butanol, freeze at -80°C for 12 hours, and freeze-dry for 24 hours. After completing the above steps, use a scanning electron microscope to observe the morphological changes of the hyphae.
[0053] Reactive oxygen species (ROS) analysis: To evaluate the effects of chitosan-copper / zinc-based hybrid nanoflower materials on the physiological state and stress response of Rhizoctonia solani, the fluorescent dye 2',7'-dichlorofluorescein diacetate (DCFH-DA) was used to analyze the reactive oxygen species (ROS) in fungal hyphae. A 7mm diameter Rhizoctonia solani mycelium block was placed in PDB medium and cultured on an oscillator at 25±2°C and 150rpm for 48h. Subsequently, the hyphae were centrifuged and washed three times with PBS buffer and resuspended in 0.1M PBS solution to obtain a hyphae suspension. After the hyphae suspension was treated in a PBS solution containing 45mg / L chitosan-copper / zinc-based hybrid nanoflower materials for 12h, it was stained with DCFH-DA. Subsequently, the samples were examined using a confocal laser scanning microscope (CLSM). Sterile dH2O was used as a negative control.
[0054] Figure 7 The effects of chitosan-copper / zinc-based hybrid nanoflowers on the mycelial morphology and reactive oxygen production of Rhizoctonia solani are shown. Figure 7 (a) and (c), scanning electron microscopy images show that chitosan-copper / zinc-based hybrid nanoflowers significantly changed the morphology of Rhizoctonia solani, resulting in obvious wrinkling on the hyphae surface. Figure 7 (b) and Figure 7 (d) All are bright field, Figure 7 (b-1) and Figure 7 (d-1) are all dark fields, control group Figure 7 No green fluorescence signal was observed in (b-1), while the mycelium exposed to chitosan-copper / zinc-based hybrid nanoflower materials showed significant green fluorescence, as shown in Figure 7 (d-1), indicating that chitosan-Cu / Zn-based hybrid nanoflower materials triggered the excessive production of reactive oxygen species in the mycelium.
[0055] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing chitosan-copper / zinc-based hybrid nanoflower material, characterized in that: The specific steps are as follows: S1: dissolving chitosan in an acetic acid solution to obtain a chitosan solution; adding a copper salt and a phosphate solution to the chitosan solution, mixing them evenly to obtain a reaction system for self-assembly reaction; washing and drying the reaction product to obtain chitosan-copper hybrid nanoflowers; S2: Disperse zinc oxide nanoparticles in an ethanol solution, add the chitosan-copper hybrid nanoflowers prepared in step S1, mix evenly and shake to react, modify the chitosan-copper hybrid nanoflowers with zinc oxide nanoparticles, wash and dry the reaction product to obtain a chitosan-copper / zinc hybrid nanoflower material.
2. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: The concentration of chitosan in step S1 is 1.25-5 mM.
3. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: In step S1, the concentration of copper ions in the reaction system is 1-40 mM, and the concentration of phosphate is 0.05-0.1 mM.
4. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: The copper salt in step S1 is copper sulfate or copper nitrate.
5. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: The pH value of the self-assembly reaction in step S1 is controlled at 7 to 8, and the reaction time is 36 to 96 hours.
6. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: The volume percentage concentration of the acetic acid solution in step S1 is 2%; the volume percentage concentration of the ethanol solution in step S2 is 20%.
7. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: In step S2, the mass ratio of chitosan-copper-based hybrid nanoflowers to zinc oxide nanoparticles is (7-20):
1.
8. The method for preparing chitosan-copper / zinc-based hybrid nanoflower material according to claim 1, characterized in that: In step S2, the shaking reaction is carried out at 25±2° C. and 180 rpm for 8 to 12 hours.
9. A chitosan-copper / zinc-based hybrid nanoflower material obtained by the preparation method according to any one of claims 1 to 8.
10. An application of the chitosan-copper / zinc-based hybrid nanoflower material according to claim 9 in agricultural antibacterial treatment, characterized in that: The chitosan-copper / zinc-based hybrid nanoflower material is sprayed onto crops infected with pathogens, wherein the concentration of the chitosan-copper / zinc-based hybrid nanoflower material is 10-100 mg / L.
